Perceiving speech from a familiar speaker engages the person identity network - Gaël Cordero; Jazmin R. Paredes-Paredes; Katharina von Kriegstein; Begoña Díaz (PLoS ONE, 2025)
Numerous studies show that speaker familiarity influences speech perception. Here, we investigated the brain regions and their changes in functional connectivity involved in the use of person-specific information during speech perception. We employed functional magnetic resonance imaging to study changes in functional connectivity and Blood-Oxygenation-Level-Dependent (BOLD) responses associated with speaker familiarity in human adults while they performed a speech perception task. Twenty-seven right-handed participants performed the speech task before and after being familiarized with the voice and numerous autobiographical details of one of the speakers featured in the task. We found that speech perception from a familiar speaker was associated with BOLD activity changes in regions of the person identity network: the right temporal pole, a voice-sensitive region, and the right supramarginal gyrus, a region sensitive to speaker-specific aspects of speech sound productions. A speech-sensitive region located in the left superior temporal gyrus also exhibited sensitivity to speaker familiarity during speech perception. Lastly, speaker familiarity increased connectivity strength between the right temporal pole and the right superior frontal gyrus, a region associated with verbal working memory. Our findings unveil that speaker familiarity engages the person identity network during speech perception, extending the neural basis of speech processing beyond the canonical language network.